Magnetic SANS study of a sintered Nd–Fe–B magnet: Estimation of defect size. (1st April 2015) - Périgo, E.A.; Gilbert, E.P.; Michels, A.
Abstract: The magnetic microstructure of an isotropic sintered Nd–Fe–B permanent magnet was studied at room temperature by means of unpolarized magnetic-field-dependent small-angle neutron scattering (SANS). Although the microstructure of the material consists of micron-sized Nd2 Fe14 B crystallites that are separated by a (low volume fraction) nanometer-sized Nd-rich phase, the SANS signal contains a significant contribution due to spin misalignment, which is evidenced by an enhanced scattering signal along the direction of the applied field. The origin of this spin misalignment is presumably related to the perturbing effect of the Nd-rich interphases. Analysis of the SANS data in terms of the autocorrelation function of the spin misalignment provides an almost field-independent length scale lC  ≅ 40 nm, which, for soft magnetic materials, is usually taken as a measure for the size of inhomogeneously magnetized regions around lattice imperfections. Comparison of our results with a phenomenological expression for lC based on micromagnetic theory suggests that the large anisotropy field of the Nd2 Fe14 B phase (which is of the order of 8 T) reduces the size of gradients in the spin microstructure, so that, for hard magnetic materials, lC represents the (field-independent) size of the characteristic defect in the microstructure.